Prevention of acute graft-versus-host disease by magnetic nanoparticles of Fe3O4 combined with cyclosporin A in murine models - Cheng J (Dove Medical Press, 2011)
Jian Cheng1,*, Ying Zhou1,*, Baoan Chen1, Jun Wang1, Guohua Xia1, Nan Jin1, Jiahua Ding1, Chong Gao1, Gouming Chen2, Yushan Miao2, Weilan Li2, Ziling Liu3, Xuemei Wang11Department of Hematology, Zhongda Hospital, Medical School, Southeast University, Nanjing, People’s Republic of China; 2Department of Pharmacy, Zhongda Hospital, Medical College, Southeast University, Nanjing, People’s Republic of China; 3The First Hospital of Jilin University, Changchun, Jilin, People’s Republic of China *These authors have contributed equally to this workObjective: To investigate the effect of magnetic nanoparticles (MNPs) of Fe3O4 combined with cyclosporin A (CsA) on acute graft-versus-host disease (aGVHD) after allogeneic hematopoietic stem cell transplantation (allo-HSCT) in murine models.Methods: BALB/c mice preconditioned with total-body irradiation generated aGVHD and then were followed with allo-HSCT from allogeneic C57BL/6. Recipient mice were randomly divided into five groups and then given different supportive care and followed up. The physical signs and median survival time (MST) were recorded, peripheral blood cell counts were assessed, and histological changes of the main tissues were evaluated with hematoxylin-eosin staining. Furthermore, fluorescence polarization immunoassay was used to monitor the concentration of CsA.Results: The irradiated-only mice developed typical aGVHD, and the typical signs of aGVHD in the skin, liver, and intestine were observed by histopathological examination. Both CsA alone and in combination with Fe3O4 MNPs significantly prolonged the MST of recipient mice compared with both the control and the Fe3O4 MNPs groups. Notably, a combination of CsA with Fe3O4 MNPs can elevate the peripheral white blood cells and alleviate the symptoms of GVHD and the pathological damage after allo-HSCT. In addition, the concentration of CsA was higher in plasma, heart, liver, and spleen of recipient mice with supporting care of the combination of CsA with Fe3O4 MNPs than with CsA alone.Conclusion: Taken together, Fe3O4MNPs may be used as a carrier of immunosuppressive agents to alleviate GVHD after allo-HSCT in murine models.Keywords: allogenetic stem cell transplantation, mice, HSCT